2023
DOI: 10.32322/jhsm.1180255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single serve sachet powder drinks on color stability of a nano-hybrid composite resin

Abstract: Aim: Nano-filled composite resin materials used for aesthetic purposes have better mechanical, polish ability, and color stability properties compared to other composite resin types. The aim of this in vitro study was to evaluate the effect of 5 different single serve sachet powder drinks popular among adolescents in recent years on the color change of Nano hybrid composite resin material. Material and Method: In this study, Nano hybrid composite resin (Filtek Z550) and five different types of sachet dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…45 It is thought that the reduction of the resin polymerization rate and the limitation of the degree of conversion after a certain time limit the positive effect of the addition polymerization. [48][49][50] As a result of this study, in which we investigated the effect of the addition polymerization process on the color stability of different types of composite resins; It was found that the addition polymerization process reduced the surface coloration.…”
Section: Discussionmentioning
confidence: 99%
“…45 It is thought that the reduction of the resin polymerization rate and the limitation of the degree of conversion after a certain time limit the positive effect of the addition polymerization. [48][49][50] As a result of this study, in which we investigated the effect of the addition polymerization process on the color stability of different types of composite resins; It was found that the addition polymerization process reduced the surface coloration.…”
Section: Discussionmentioning
confidence: 99%